Způsoby tvoření obchodních značek - Tichá, Veronika (Univerzita Pardubice, 2012)
The aim of this paper is to describe word-formation and to analyse the sample of trademarks.
Formation of trademarks
Keywords: tvorba slov; brand management; obchodní názvy; word-formation; brand management; trademarks